Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1086/681620
|View full text |Cite
|
Sign up to set email alerts
|

Competition for Light and Nutrients in Layered Communities of Aquatic Plants

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Online enhancement: appendixes.abstract: Dominance of free-floating plants poses a threat to biodiversity in many freshwater ecosystems. Here we propose a theoretical framewor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…Non‐native plants, for instance, often differ in phylogeny from natives, which can provide a competitive advantage (Hill and Kotanen , Parker et al ). Furthermore, the growth strategy of plants is generally phylogenetically determined (Scharfy et al ) and the growth strategy can make certain invaders more dominant, for example forbs over graminoids, or floating over submerged plants (Scharfy et al , van Gerven et al ). Although multiple factors control variation in secondary metabolites in concert, they are often studied separately.…”
mentioning
confidence: 99%
“…Non‐native plants, for instance, often differ in phylogeny from natives, which can provide a competitive advantage (Hill and Kotanen , Parker et al ). Furthermore, the growth strategy of plants is generally phylogenetically determined (Scharfy et al ) and the growth strategy can make certain invaders more dominant, for example forbs over graminoids, or floating over submerged plants (Scharfy et al , van Gerven et al ). Although multiple factors control variation in secondary metabolites in concert, they are often studied separately.…”
mentioning
confidence: 99%
“…Because floating and submerged plants have different positions in the water column, the competition for both light and nutrients in the substrate becomes asymmetric [13]. Van Gerven et al [42] found that floating plants always outcompete submerged plants when there is an adequate supply of light and nutrients. Moreover, an increasing nutrient level leads to an advance of free-floating species in competition with submerged macrophytes; this effect is also found in both field and mesocosm studies [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…S1). The model is based on theoretical frameworks for resource competition (Huisman and Weissing 1995;Van Gerven et al 2015a) and simulates the dynamics of plant biomass (gDW m -2 ) and the N and P concentrations (gN m -3 and gP m -3 ) in the water (Eqs. 3.1-3.4).…”
Section: Methodsmentioning
confidence: 99%
“…The critical nutrient loading is not only relevant to systems that possess alternative stable states such as shallow lakes, but also applies to systems that are not likely to have alternative stable states but still can be subject to abrupt shifts, such as ditches (Van Gerven et al 2015a). The critical nutrient loading of both ditches and shallow lakes was found to depend on system characteristics like water depth, sediment type and water flow Van Liere et al 2007).…”
Section: Introductionmentioning
confidence: 99%